Reorientation Of Islamic Higher Education Leaders in Dealing With The Global World - Widhiya Ninsiana; M. Ihsan Dacholfany (Al-Ulum, 2017)
This article focuses on the role of Islamic Higher Education in ecnoutering globalization. In this study, the authors suggest that in order to support the efforts for development and progress of a nation, Islamic Higher Education must have a link between the world of science, technology, and the needs of a society. These efforts are visible by fostering and producing qualified human resources, having knowledge and technology insight with a provision of faith piety that remains based on religious values, morals, and noble morals in accordance with the norms of religious and governmental rules so as to master, develop and apply what is gained from Islamic higher education. Vision and mission of Islamic Higher Education are achievable with strong lingkage among lecturers and students, employees and graduates are implemented in accordance with the objectives and demands of th stakeholders or markets.